2021
DOI: 10.1088/1748-0221/16/10/p10015
|View full text |Cite
|
Sign up to set email alerts
|

Special features of manufacturing cutting inserts from nanocomposite material Al2O3-SiC

Abstract: The article examines the cutting characteristics of the developed composite material based on aluminum oxide micropowders with silicon carbide nanopowder additives obtained with the help of electric sintering. The influence of thermal conductivity of the developed composite Al2O3-SiC based material on the wear and durability of the material in application of cutting tool is examined, and a comparison with the traditional cutting ceramic tool materials is made. Considering that the process of cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The effect of the phase content and morphology of initial powder particles has been considered by researchers, too [ 19 , 20 ]. In the paper [ 21 ], it is reported that a fine-grain matrix was formed due to the dissociation of zircon and silica reactions, as well as bonding of the finer fractions of alumina and mullite powders, and the products of zircon dissociation, where a liquid phase is most likely involved.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the phase content and morphology of initial powder particles has been considered by researchers, too [ 19 , 20 ]. In the paper [ 21 ], it is reported that a fine-grain matrix was formed due to the dissociation of zircon and silica reactions, as well as bonding of the finer fractions of alumina and mullite powders, and the products of zircon dissociation, where a liquid phase is most likely involved.…”
Section: Introductionmentioning
confidence: 99%
“…Керамика Al 2 O 3 −SiC широко используется в промышленности в качестве износостойких пар трения, режущего инструмента, элементов керамической защиты и др. [1][2][3]. Частицы SiC позволяют повысить механические свойства оксида алюминия за счет торможения миграции границ зерен и формирования сжимающих внутренних полей напряжений, изменяющих характер разрушения керамики [4][5][6][7][8][9].…”
Section: Introductionunclassified
“…Alumina-based ceramics are popular materials for cutting tools due to their good wear resistance, high hardness, heat resistance and chemical stability [ 2 ]. There are many reports on the effects of various reinforcements, such as graphene [ 3 ], SiC [ 4 , 5 ], SiC w -Si 3 N 4 [ 6 ], TiC [ 7 ], TiC-TiN [ 8 ] and WC [ 9 ], and the works on property improvement are still going on. Basically, sintering methods are used for the fabrication of ceramic matrix composites [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%